The Relationship Between Knowledge And Attitude Towards The Preventive Behaviors For The Covid-19 Transmission In Pregnant Mothers At “Rini K” Independent Midwifery Practice (PMB), Jagakarsa, South Jakarta, 2021 - Rini Kundaryanti; Karningsih Karningsih; Hetty Astri; Syafrudin Syafrudin (Universitas STRADA Indonesia, 2021)
The pregnant mothers’ knowledge and attitude towards Covid-19 transmission prevention are still categorized as poor so pregnant mothers need to know about preventing Covid-19 transmission. This study aimed to know the relationship between knowledge and attitude towards the preventive behaviors for the Covid-19 transmission in pregnant mothers. This study used a cross-sectional approach. The samples were 73 1st trimester pregnant mothers as the respondents. The data collection was done using a questionnaire that passed the validity and reliability test. Respondents who behaved well 51 (69.9%), had good knowledge 40 (54.8%) and who had a positive attitude 30 (41.1%) and a p value of 0.05 on the knowledge and attitude variables. There is a relationship between knowledge and attitudes towards the behavior of preventing the transmission of Covid-19 in pregnant women.